2013
DOI: 10.1111/hiv.12104
|View full text |Cite
|
Sign up to set email alerts
|

Risk of clinically significant depression in HIV‐infected patients: effect of antiretroviral drugs

Abstract: ObjectivesWe aimed to characterize depression in newly diagnosed HIV-infected patients, to determine the effect of antiretroviral therapy (ART) on its incidence, and to investigate whether efavirenz use was associated with a higher risk, compared with non-efavirenz-containing regimens, in the Spanish CoRIS cohort. MethodsCoRIS is a contemporary, multicentre cohort of HIV-infected patients, antiretroviral-naïve at entry, launched in 2004. Poisson regression models were used to investigate demographic, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…Efavirenz, a frequently prescribed non-nucleoside reverse-transcriptase inhibitor, is known to have neurological side effects. We therefore performed preliminary analyses of time-updated/lagged regimen types by drug classes and by use of efavirenz but, as other studies suggest, we also did not find evidence for associations with incident depression [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 94%
“…Efavirenz, a frequently prescribed non-nucleoside reverse-transcriptase inhibitor, is known to have neurological side effects. We therefore performed preliminary analyses of time-updated/lagged regimen types by drug classes and by use of efavirenz but, as other studies suggest, we also did not find evidence for associations with incident depression [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 94%
“…Notably, the prevalence of documented depression in this study (5.6% of women in the cohort and 17.0% of men) differs from that reported in other cohorts (56.1% of HIV-positive women with depressive symptoms in the Women’s Interagency HIV Study compared to 21.0% of HIV-positive men in the Multicenter AIDS Cohort Study [ 26 ]), suggesting that depression may have been underascertained among female neuro-AIDS patients in this study and/or that neuro-AIDS severity and progression in female patients precluded psychiatric diagnoses. Notably, a recent cohort study assessing the impact of ART on clinically significant depression in the Spanish AIDS Research Network also found no statistically significant difference in the incidence of depression between male and female participants, although there was a non-significant trend favoring a higher incidence among women (adjusted incidence rate ratio = 1.45, 95% CI: 0.96–2.18, p = 0.074) [ 27 ]. While the findings regarding sex, depression, and survival in the current study should be interpreted with caution, additional research should certainly be undertaken to explore this relationship further.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread clinical use of antiretroviral drugs has improved the survival time of HIV-1-infected patients significantly. 3,4 HIV-1/AIDS is becoming a chronic disease that can be gradually controlled. 5 In China, approximately 50 000 patients are newly diagnosed with HIV-1 yearly.…”
Section: Introductionmentioning
confidence: 99%